Collision Tumor of Basal and Squamous Cell Carcinoma of the Palm - Lam, Charlene (J Clin Aesthet Dermatol, 2019)
Nonmelanoma skin cancers, typically induced by ultraviolet light, are rarely found on the palmar aspects of the hands. Here, we describe a case of a basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) collision tumor on the palm of a 71-year-old woman. A brief review of literature regarding basal cell carcinoma of the palm and hand are provided, including etiology, diagnosis, and treatment recommendations.